Aportes para la comprensión de la arquitectura jurídica de la relación de consumo en el derecho brasilero - Catalan, Marcos (2018)
The Brazilian Consumer Protection and Defense Act has granted special protection to several categories. In doing so it has in fact recognized the stricto sensu, the bystander, and the collectively protected categories, further  associating prospective protection to all those who may be reached by any number of commerce practices. It has also not waived rights of collective bargaining for consumer demands as fundamental rights. This article seeks to explore whether the current theoretical background that aims to categorize collectives as consumers is enough to deal with the issues within the field. Our hypothesis is that the current background is not sufficient given the need to overcome, through a complex hermeneutic approach, the answers proposed by the dogmatic perspective within consumer studies. Our approach seeks to critically analyze the juridical literature written on the topic in Brazil, mapping decisions written during the almost 30 years of effectivity of the Brazilian Consumer Protection and Defense Act, reviewing each of the current theories on the issue of consumer protection, and finally proposing an overarching theory of consumer protection.